Evidence-Based Behavioral Treatment of Dog Phobia With Young Children: Two Case Examples. (January 2013) - May, Anna C.; Rudy, Brittany M.; Davis, Thompson E.; Matson, Johnny L.
Specific phobias are among the most common anxiety disorders, especially in children. Unfortunately, a paucity of literature exists regarding the treatment of specific phobia in young children, despite the knowledge that traditional techniques (i.e., cognitive-behavioral therapy [CBT]) may not be practical. Therefore, the purpose of this article is to present two case studies that provide empirical support for the evidence-based behavioral treatment of specific phobia with young children (ages 4 and 5 years). Results indicated that following 10 to 13 sessions of graduated exposure therapy using reinforced practice and participant modeling, the children no longer met criteria for clinically significant phobias of dogs. Treatment effects were maintained at 7-month follow-up despite reported lack of practice and/or regular exposure to dogs in the children's daily lives.